Bathurst Inlet Lodge, Nunavut -- photograph ... - Seale, Linda N. (University of Alberta Library, 2001)
Bathurst Inlet Lodge, Nunavut, is the former Hudson's Bay Company trading post. HBC buildings are distinguished by the black four sided roof, red and white paint, and the white stones lining pathways. The Nunavut territorial flag is on the left. The Lodge, and the houses for several Inuit families, are generally used only in the summer months. Photograph taken June 2001. ...